Smoke and heat flow in a large volume building in case of fire - Węgrzyński, Wojciech (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
In the paper the author presents some chosen methodologies used in the design process of natural smoke and heat ventilation systems and the use of Computational Fluid Dynamics (CFD) tools. Comparison of the performance of various systems was conducted on the basis of performed CFD analyses. The analysis was prepared with the use of ANSYS Fluent 14.5 package, with the use of RNG k-ε turbulence model. The results of analysis are presented, together with the additional design recommendations.